A tractroid realization of a 2d black hole vacuum - Williams, Floyd L (Annals of Mathematics and Physics, 2022)
The two-dimensional black hole vacuum obtained from a spatial slice of the BTZ black hole is mapped explicitly to a tractroid surface minus a bounding circle.